Characteristics of Corporate Executives: A Research Note - Price, Karl F. (Academy of Management Journal, 1972)
The article presents a study on particular characteristics of executives in high technological industries compared to those in lower technology industries. The hypotheses of the study were that the level of technology in the industry related to an executive's age, level of education, technical level of education, and job mobility. It was found that there are no significant relation between and executive's age or level of education and on the level of technology in their industry. However, executives in higher technology industries did exhibit a higher level of technological education and job mobility.